2011
DOI: 10.1111/j.1751-7893.2011.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in antipsychotic naïve patients diagnosed with schizophrenia

Abstract: Findings of the present study suggest that although only few antipsychotic naïve patients diagnosed with schizophrenia have MS, a significantly large proportion of patients have subsyndromal MS. Awareness of this in clinicians can have implications in the selection of antipsychotic medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 57 publications
2
27
1
Order By: Relevance
“…Of the studies which were published from the same center thus representing similar population, the prevalence of Met-S was much lesser in antipsychotic naïve patients as compared to patients who were already on treatment (Grover et al, 2012a;Grover et al, 2012b, Grover et al, 2014a. Similar results were also noted in study by Pallava et al (2012).…”
Section: Medicationssupporting
confidence: 83%
“…Of the studies which were published from the same center thus representing similar population, the prevalence of Met-S was much lesser in antipsychotic naïve patients as compared to patients who were already on treatment (Grover et al, 2012a;Grover et al, 2012b, Grover et al, 2014a. Similar results were also noted in study by Pallava et al (2012).…”
Section: Medicationssupporting
confidence: 83%
“…[262728] Grover et al .,[27] investigating MetS in S-DN patients, found elevated blood pressure (>135/85 mm/Hg) in 26% of the cases. In another study, Fernandez-Egea et al .,[28] reported significantly higher pulse pressure but no significant difference in systolic or diastolic blood pressure while comparing S-DN patients with FEP and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of MetS in S-DN patients varies from as low as 3.3% to as high as 26% in various studies. [2731323334] While most study populations belonged to the age group of 20s or early 30s, the sample size varied widely (30-400). Methodological issues like definition of MetS used, ethnicity and inclusion criteria might explain this huge variation.…”
Section: Discussionmentioning
confidence: 99%
“…patients fulfilling one to two criteria of MS) and have reported that 30 % patients fulfilled two criteria and 41 % fulfilled one criterion of MS . These studies also show that prevalence of MS is high in those who are married, of higher age and have higher level of education (Grover et al 2012d). In a series of longitudinal studies involving drug-naïve patients with schizophrenia, authors reported baseline prevalence of MS to vary from 3.3 to 9.5 %, which increased to 32-52 % after 3 months of antipsychotic treatment (Sahoo et al 2007a, b;, with the highest increase seen in patients receiving olanzapine, followed by risperidone, and least with haloperidol (Sahoo et al 2008).…”
mentioning
confidence: 85%
“…Many studies from India have evaluated the prevalence of MS in patients with schizophrenia. Cross-sectional studies from India, which have evaluated drug-naïve patients with schizophrenia, have reported prevalence rates to vary from 4 to 26 % among them (Padmawati et al 2010;Pallava et al 2012;Grover et al 2012d). Studies, which have compared drugnaïve patients with healthy control groups, have in general reported lower prevalence in the drug-naïve patients compared to healthy control groups (Grover et al 2012d).…”
mentioning
confidence: 95%